2013
DOI: 10.1071/sh12143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of lymphogranuloma venereum among men who have sex with men at a Sydney metropolitan sexual health clinic

Abstract: During an 18-month period to June 2012, 1732 anal chlamydia (Chlamydia trachomatis) tests were performed among men who have sex with men (MSM) at RPA Sexual Health in Sydney's inner west. Positive anal chlamydia samples were subsequently tested for lymphogranuloma venereum (LGV). Seventy-five (4.3%) anal samples were positive for chlamydia among 67 men during the study period. Anal symptoms were reported for 16 out of 75 (21.3%) of anal chlamydia episodes overall. Three episodes of LGV (all serovar L2b) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…61,63,65 Although LGV has been identified in the pharynx of MSM overseas, 60,66 a single Australian study failed to identify any cases. 63 Urethral LGV was recently identified in over 2% of MSM with anorectal LGV and almost 7% of their contacts at an Amsterdam clinic, 67 with around half of these infections being asymptomatic.…”
Section: Lymphogranuloma Venereummentioning
confidence: 99%
See 1 more Smart Citation
“…61,63,65 Although LGV has been identified in the pharynx of MSM overseas, 60,66 a single Australian study failed to identify any cases. 63 Urethral LGV was recently identified in over 2% of MSM with anorectal LGV and almost 7% of their contacts at an Amsterdam clinic, 67 with around half of these infections being asymptomatic.…”
Section: Lymphogranuloma Venereummentioning
confidence: 99%
“…This contrasts with other European data, where a large proportion of asymptomatic anorectal chlamydia has been identified as LGV. 59,60 Anorectal LGV has been identified among Australian MSM in both clinic 61,62 and community-based 63,64 settings. In common with most overseas reports, Australian cases predominantly affect HIV-positive MSM, with symptoms of proctitis.…”
Section: Lymphogranuloma Venereummentioning
confidence: 99%
“…8 Studies in NSW between 2005 and 2012 identified all cases of LGV in GBM were caused by the L2b serovar. [9][10][11][12] In developed countries, LGV is transmitted primarily through condomless anal intercourse and is commonly associated with HIV, syphilis, gonorrhoea and hepatitis C infections. 1 The use of recreational drugs along with the erectile dysfunction medication sildenafil suggests that certain Australian subgroups of sexually adventurous GBM are at greatest risk of LGV.…”
Section: Introductionmentioning
confidence: 99%
“…Condomless receptive anal sex is also associated with an increased risk of anorectal chlamydia [9, 10]. However, anorectal chlamydia is not usually associated with genital ulceration [11, 12]. Syphilis is also associated with condomless receptive anal sex [13].…”
Section: Introductionmentioning
confidence: 99%